Gaya Kepemimpinan K.H. Tatang Astarudin dalam Menumbuhkan Akhlak Mulia di Kalangan Santri - Razak, Hery Catur; Muhlis, Atjep; Fakhruroji, Moch (Tadbir: Jurnal Manajemen Dakwah, 2021)
This paper aims to find out how communication styles, motivations are given and ways of making decisions K.H. Tatang Astarudin, in cultivating noble character among students. The method used in this research is descriptive, through observation and interviews as a step to collect data, and analyze with qualitative means. The results of the research obtained that in cultivating noble character among students cannot be separated from the role of a leader with a democratic and charismatic leadership style. In democratic leadership, it is demanded not to make decisions in an arbitrary or one-sided manner, because in a democratic leadership the emphasis is on leadership who can hear the aspirations and sound the nature of deliberation. Charismatic is a style of leadership that can take sympathy. Communication and motivation also play an important role in shaping a good personality.